Time-Images in Don DeLillo’s Writing: A Reading of The Body Artist, Point Omega and Zero K - Andrea Pitozzi (Transatlantica)
This article focuses on the most recent writings of Don DeLillo, and in particular it analyzes three of DeLillo’s later works, namely The Body Artist, Point Omega and Zero K, as examples of a more meditative and reflective attitude towards the themes of time and image in his recent production. By studying how these books present the reader with a sort of suspended narrative time, I will read them in the light of concepts and notions drawn from the philosophy of Henri Bergson and Gilles Deleuze, in particular Bergsonian duration and Deleuze’s idea of the time-image. Reading DeLillo’s recent novels according to this philosophical framework enables one to consider the implications his writing draws between time and images in configuring the perception of time as an almost physical, substantial and non-subjective whole to be sensed and described through narrative and figurative strategies.